Otimização da estrutura e das propriedades luminescentes de materiais híbridos Eu3+:siloxano– polimetacrilato a serem aplicados em fotônica - Jesus, Filipe Augusto de (2019)
In this thesis, the influences of experimental parameters on the structure and the luminescent properties of Eu3+:siloxane-polymethacrylate hybrid materials were analyzed. These materials were synthesized by combination of sol-gel process with radical polymerization and doped with hexahydrated europium(III) chloride. The organic phase composition, the dopant amount in the hybrid, the polymeric content and the inorganic phase proportion were tuned and, as result, a significant enhancement of the luminescence of the hybrid was achieved. In the first step of the work, the sample with poly(methyl methacrylate) in the organic phase was more suitable for Eu3+ emission, owing to: the lower interaction of the dopant ions with luminescence quenching groups, the larger radiative emission rate and the higher quantum efficiency. The analysis of Eu3+ coordination in the hybrids demonstrated the preferential occupation of sites in which there are interactions with carbonyls of polymeric chains, however, europium(III) clusters are formed when the host coordination ability is overcomed. These clusters are deleterious to luminescent processes because they favor the ion–ion energy transfer by non-radiative mechanisms, which resulted in decreases of lifetimes, radiative emission rates and quantum efficiencies of Eu3+ emission. In turn, the increase in the polymer/silica proportion promoted the more efficient dispersion of Eu3+ ions in the hosts and modified the chemical environment by the presence of more carbonyl groups at Eu3+ coordination sphere in hybrids with higher polymeric contents. These changes modified the profiles of emission decay curves, raised the radiative emission rate and increased the quantum efficiency of the hybrids with higher polymer content. In the last step of this work, the results indicated that the moderate proportion of inorganic structures in the composition of the samples is not deleterious to the emission processes, which occurs only when this parameter is very high. In short, the structure and the emission properties of Eu3+:siloxane-polymethacrylate hybrids were optimized by tuning the experimental parameters, achieving a huge quantum efficiency increase from 9,7 % in PHEMA hybrid to 35,2 % in TEOS0.